Maintaining the balance between the protection of human beings and the pressure for efficiency. The axiological foundations of labor law in the era of algorithmic management - Barłóg, Miłosz (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The development of digital technologies in the management of labor processes exacerbates the conflict between the protective function of labor law and the drive to maximize productivity. The traditional labor model, based on the protection of employee dignity, privacy and autonomy, is beginning to give way to systems focused on measurable results, which can lead to simplified decisions and an increase in power asymmetry in favor of the employer. In view of this, an appropriate legal response is needed to restore the balance between the classical values of labor law and practice under conditions of increasing algorithmization. The article focuses on analyzing the axiological aspects of the changes taking place in the labor environment, and on identifying areas of conflict and potential mechanisms to effectively safeguard the interests of the parties to the employment relationship.